2019
DOI: 10.1097/01.aog.0000558717.21780.b6
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Climate-Change Related Exposures on Obstetrics Outcomes [18G]

Abstract: INTRODUCTION: Toxic environmental exposures, specifically climate-change related exposures, pose a unique risk to pregnant women and the developing fetus. Robust evidence analysis is needed to guide clinicians on risk assessment and clinical counseling. METHODS: A literature search was conducted by our research team and medical librarian; scope included United States studies from 2007 to 2017. Climate-change related exposures included air pollution comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The role of coexposures, especially to air pollution, is one of the many unresolved questions in this area. Some evidence suggests that exposure to high levels of various outdoor air pollutants may increase the risk of congenital heart defects35 as well as adverse birth outcomes and other pregnancy complications 4. Meanwhile, hotter days are associated with higher concentrations of ground-level ozone 36…”
Section: Challenges Caveats and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of coexposures, especially to air pollution, is one of the many unresolved questions in this area. Some evidence suggests that exposure to high levels of various outdoor air pollutants may increase the risk of congenital heart defects35 as well as adverse birth outcomes and other pregnancy complications 4. Meanwhile, hotter days are associated with higher concentrations of ground-level ozone 36…”
Section: Challenges Caveats and Recommendationsmentioning
confidence: 99%
“…Several epidemiological studies over the past five years have reported associations between high temperatures and adverse pregnancy outcomes, including preterm birth, stillbirth, and low birth weight (LBW),3 , 4 as well as congenital heart defects 5. (At least two studies have also examined ambient temperature in relation to neural tube defects 6 , 7…”
mentioning
confidence: 99%
“…Elevated temperatures and prolonged heat waves during pregnancy can have significant repercussions on breastfeeding. In an extremely hot climate, pregnant women face an increased risk of premature birth, stillbirth, low birth weight, and pre-eclampsia (Bekkar et al, 2020; DeNicola et al, 2019; Lusambili & Nakstad, 2023). Premature birth could have direct effects on a parent’s ability to breastfeed as infants may require advanced or critical care, parents may be unable to express sufficient milk for their vulnerable newborns, and low birth weight may lead to concerns about weight gain and the need for supplementation, and result in over-reliance on commercial milk formula.…”
Section: Multidimensional Climate Influences and Human Healthmentioning
confidence: 99%
“…Warmer temperatures are also associated with preterm birth, low birth weight and stillbirth. [32][33][34]…”
Section: General Practice In the Era Of Planetary Healthmentioning
confidence: 99%